2020
DOI: 10.1038/s41416-020-01086-y
|View full text |Cite
|
Sign up to set email alerts
|

BCAS2, a protein enriched in advanced prostate cancer, interacts with NBS1 to enhance DNA double-strand break repair

Abstract: Background Breast cancer amplified sequence 2 (BCAS2) plays crucial roles in pre-mRNA splicing and androgen receptor transcription. Previous studies suggested that BCAS2 is involved in double-strand breaks (DSB); therefore, we aimed to characterise its mechanism and role in prostate cancer (PCa). Methods Western blotting and immunofluorescence microscopy were used to assay the roles of BCAS2 in the DSBs of PCa cells and apoptosis in Drosophila, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Reduced adult neurogenesis in hippocampus of BCAS2 cKO mice Previously, we found that BCAS2 regulated b-catenin [5,9]. The Wnt/b-catenin signaling pathway participates in hippocampal neurogenesis [14,15,22].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Reduced adult neurogenesis in hippocampus of BCAS2 cKO mice Previously, we found that BCAS2 regulated b-catenin [5,9]. The Wnt/b-catenin signaling pathway participates in hippocampal neurogenesis [14,15,22].…”
Section: Resultsmentioning
confidence: 91%
“…Association of BCAS2 and b-catenin in the hippocampus BCAS2 regulates b-catenin expression [5,9] and BCAS2 could regulate adult neurogenesis (Fig. 2 and 4), so we examined the association between BCAS2 and b-catenin in adult neurogenesis.…”
Section: Reduced Adult Neurogenesis In Hippocampus Of Mice With Bcas2 Knockdownmentioning
confidence: 99%
See 2 more Smart Citations
“…69 Breast carcinoma-amplified sequence 2 ( BCAS2 ) takes part in DNA repair, cell cycle control, apoptosis and tissue homoeostasis. 70 On the other hand, GRB14 , ARG1 and BRE appeared as downregulated genes. A possible role of GRB14 for the proliferation of human breast and prostate cancers, 71 as well as functions of ARG1 in tumor immunity, tumor proliferation and metastasis, were previously reported.…”
Section: Resultsmentioning
confidence: 95%